Cup‐Cage Solution for Massive Acetabular Defects: A Systematic Review and Meta‐Analysis - Wang, Chao‐xin; Huang, Zi‐da; Wu, Bai‐jian; Li, Wen‐bo; Fang, Xin‐yu; Zhang, Wen‐ming (Orthopaedic surgery, 2020)
Our systematic review compiled multiple studies and evaluated survivorship and clinical outcomes of cup‐cage construct usage in the management of massive acetabular bone defects. This systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. Various combinations of “acetabular”, “pelvis”, “cup cage” and their corresponding synonyms were used to search relevant articles in the Cochrane, EMBASE, and PubMed databases. Basic information of the functional scores, implant revision rate, and complication rate were selected as outcomes for analysis. Finally, a total of 11 articles published between 1999 and 2019 were selected, which include 232 patients with an average age of 68.5 years (range, 30–90). The mean follow‐up period was 48.85 months (range, 1–140). Our study shows that the cup‐cage construct has a good clinical outcome with a low revision rate and a low complication rate. Improved clinical outcomes of cup‐cage constructs were seen with a revision rate of 8% and an all‐cause complication rate of 20%. The most commonly reported complication was dislocation, followed by aseptic loosening, infection, and nerve injuries. In summary, it is a promising method for managing large acetabular bone defects in total hip revision.